A Restricted Version of Wythoff’s Game - Liu, Wen An; Li, Haifeng; Li, Bei (The Electronic Journal of Combinatorics, 2011)
E. Duchêne and S. Gravier present the following open problem: In Wythoff’s game, each player can either remove at most R tokens from a single heap (i.e. there is an upper bound R on the number of removing tokens), or remove the same number of tokens from both heaps but there is no upper bound on the number of removing tokens. This open problem is investigated and all its P-positions are given.